MENINGKATKAN MINAT BELAJAR PADA PEMBELAJARAN BAHASA INDONESIA KELAS XI8 SMAN 2 KUPANG MELALUI MEDIA AUDIO VISUAL - Dasilva, Benedikta Yuliana Rini; Nai, Firmina Angela; Pono, Chatrina (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2024)
In class XI8 of SMAN 2 Kupang, students showed low interest in learning Indonesian. The purpose of this study was to make students more interested in learning by using audio visual media. A two-cycle classroom action research (PTK) was used. 30 students of class XI8 were the research subjects. Learning interest questionnaire, learning outcome test, and observation were used to collect data. The results of the study were analyzed descriptively by calculating students' average learning interest and learning outcomes each cycle. The results showed that students' interest in learning increased significantly, from 47.5% in the first cycle to 75% in the second cycle. Students' average learning outcomes also increased, from 55% in the first cycle to 85% in the second cycle. The results suggest that teachers should use audio-visual media when teaching Indonesian to increase student engagement and teaching effectiveness.